Peran Teknologi dalam Perencanaan dan Evaluasi Pembelajaran Teknik Elektro di Era Revolusi Industri 4.0 - Darmayanti, Rimelda Putri; Hapsoh, Widiyani Putri; Syifasari, Sally Maytita; Fua'din, Ahmad (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
This research aims to investigate the role of technology in planning and evaluating electrical engineering learning in the Industrial Revolution 4.0 era. By using a literature study approach, case study, and qualitative methods with descriptive data presentation, this research collects information about the use of technology in electrical engineering learning through observation and document analysis. The results of the analysis show that the integration of technology in learning planning and evaluation has a significant impact on learning effectiveness, by enabling the formation of an interactive and collaborative learning environment, the development of innovative teaching materials, the use of learning management systems, the adoption of project or problem-based learning models, as well as data analysis for personalization of learning. The implications of this research are to provide valuable insight for the development of best practices in utilizing technology to improve electrical engineering learning in this ever-evolving era.